Interpreting Hashtag Politics : Policy Ideas in an Era of Social Media - Jeffares, Stephen; SpringerLink (Online service). (London : Palgrave Macmillan UK, 2014)
Why do policy actors create branded policy ideas like Big Society and does launching them on Twitter extend or curtail their life? This book reveals how policy analysis can adapt in an increasingly mediatised to offer interpretive insights into the life and death of policy ideas in an era of hashtag politics.
Keywords: Science; Science, general